Comparative efficacy of C‐MAC® Miller videolaryngoscope versus McGrath® MAC size "1" videolaryngoscope in neonates and infants undergoing surgical procedures under general anesthesia: A prospective randomized controlled trial. Issue 10 (16th July 2021) - Gupta, Anju; Singh, Pooja; Gupta, Nishkarsh; Kumar Malhotra, Rajeev; Girdhar, Kiran Kumar
Abstract: Background: Various anatomical and physiological factors make intubation in infants challenging. C‐MAC videolaryngoscope shows better results as compared to the conventional direct laryngoscopy for intubation in infants. McGrath MAC size‐1 with a disposable Macintosh type blade has recently been introduced for use in infants and has not been formally evaluated in this population. Aims: This study aims to evaluate the intubation characteristics of C‐MAC Miller and McGrath MAC in neonates and infants with the primary objective to compare the time with the two devices. Methods: After informed consent from the parents, 140 neonates and infants scheduled for surgical procedures were randomized to undergo intubation with either C‐MAC Miller or McGrath MAC after standard general anesthesia. The two devices were compared in terms of total intubation time, Percent of Glottic Opening score, Cormack Lehane grades, time to glottis view, intubation difficulty score, overall success rate, first attempt success rate, and complications. Results: The median glottic view time (6 s [4–9] vs. 6 s [4–9]; p = .40) and intubation time (27 s [25.5–28] vs. 27 s [24.5–29.5]; p = .87) were similar. The mean difference (95% CI) in time to tracheal intubation and time to glottic view was 0.49 s [−3.1 to 2.1] and −1.7 s [−3.8 to 0.47], respectively. However, the Percent of Glottic Opening score, Cormack Lehane grades, and subjective intubation difficulty were significantly better with C‐MAC. The first attempt success rates, overall success rates (100% vs. 97.5%), and intubation difficulty scores were comparable. There were two failed intubations with McGrath which were successfully intubated with C‐MAC. Conclusion: The C‐MAC Miller blade showed similar intubation timings, success rates, and intubation difficulty score as compared to McGrath MAC in neonates and infants, though the former provided superior glottic views. Both the videolaryngoscopes may be safely used in infants and neonates for routine intubation scenarios.